Comparison of diagnostic criteria in patients with amyotrophic lateral sclerosis - the contribution of electromyographic findings - Dominović-Kovačević Aleksandra; Račić Duško; Grgić Sanja; Vukojević Zoran; Milanović Slađan D.; Ilić Tihomir V. (Vojnosanitetski Pregled)
Background/Aim. Diagnosis of amyotrophic lateral sclerosis (ALS) is based on combination of clinical signs and electrophysiological correlates of pathological process which takes place in general. New electrophysiological criteria Awaji-Shima (AS) additionally qualify the complex fasciculations and neurogenically modified potentials of motor units as signs of active lesions of peripheral motor neuron, contrary to previously valid revised El Escorial criteria (rEE). The objective of this research was to determine the clinical significance and advantages of using the AS criteria in patients with ALS. Methods. Thirty patients (59.2 ± 10.9 years, 57% of them with spinal form of the disease) with clinically suspected ALS were monitored from the time of diagnosis until reaching the category of definitive diagnosis or death. The clinical evaluation and electromyographic (EMG) examinations were carried out at 3-month intervals. Results. By applying the AS criteria, the category of probable or definite diagnosis was achieved in all patients with ALS, except in one (96.6%), as contrary to the rEE (33.3%), after 6 months of the follow-up period. The subclinical affection in more than two body regions has been defined through detection of denervation potentials (80% of the patients by using the AS, or 67% by the rEE criteria). The complex fasciculations were registered particularly often in small muscles of the feet (37– 40%). Conclusion. Application of the AS criteria improve the achievment of category of probable or definite diagnosis of ALS by 2.7 months earlier compared to the rEE. This outcome is particularly affected by a higher frequency of positive EMG findings, when the AS criteria were employed. Early determination of diagnosis provides the better perspective and more frequent participation of the ALS patients in pharmacotherapy studies intended to establish new therapeutic options. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 41014]